Advanced X-ray shielding and antibacterial smart multipurpose fabric impregnated with polygonal shaped bismuth oxide nanoparticles in carbon nanotubes via green synthesis. Issue 2 (3rd April 2021) - Verma, Sarika; Mili, Medha; Sharma, Charu; Bajpai, Harsh; Pal, Kunal; Qureshi, Dilshad; Hashmi, S. A. R.; Srivastava, A. K.
ABSTRACT: Synthesis of multifunctional hybrid materials for X-rays' attenuation is attracting more recognition recently because of several superiorities over the conventional radiation shielding materials made using toxic lead-based compounds. For the first time*, the present study investigates the microwave irradiation based green synthesis and in-situ stabilization of bismuth oxide (Bi2 O3 ) nanoparticles on multiwalled carbon nanotubes (MWCNT) by a novel approach for making advanced material. TEM and XRD studies have shown that nanoparticles have a uniform size with polygonal morphology and are impregnated on MWCNT. The developed hybrid nanocomposite's physical appearance is gel-like. It was then applied on a cotton fabric piece to create a multifunctional material and valuable for the fabrications of aprons, bandages, and X-ray shielding caskets. The porous nature of cotton fabric has facilitated the adhesion and stabilization of the nanocomposite. The elemental composition and topology of the hybrid material were further analyzed by XPS, EDX and AFM studies, respectively. The higher attenuation characteristics and shielding efficiency of the developed material are due to the dual shielding effect of polygonal nanoparticles and MWCNT. Availability of metal atoms with higher valency allowed the higher photoelectric effect followed by the Compton effect during X-ray shielding. GRAPHICAL ABSTRACT: UF0001